1987
DOI: 10.1044/jshr.3003.343
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Preservation in Alzheimer's Disease

Abstract: Language ability of 20 patients with probable Alzheimer's disease (AD) was evaluated. Analysis of spontaneous speech revealed a normal range and frequency of syntactic constructions but poor lexical use. A writing task showed a similar divergence, with the ability to use syntactic cues significantly more intact than the ability to use semantic cues. The results are taken to indicate that syntactic ability is selectively preserved in AD. These findings are consistent with a modular theory of grammar and of ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1
4

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 22 publications
5
101
1
4
Order By: Relevance
“…A number of studies have indicated that DAT individuals have a decreased ability to use context to disambiguate words (Balota & Duchek, 1991;Cushman & Caine, 1987;Kempler et al, 1987). We have also found that DAT individuals can take advantage of contextual constraints to enhance the appropriate meanings of ambiguous words.…”
Section: Dat and Comprehensionmentioning
confidence: 73%
See 1 more Smart Citation
“…A number of studies have indicated that DAT individuals have a decreased ability to use context to disambiguate words (Balota & Duchek, 1991;Cushman & Caine, 1987;Kempler et al, 1987). We have also found that DAT individuals can take advantage of contextual constraints to enhance the appropriate meanings of ambiguous words.…”
Section: Dat and Comprehensionmentioning
confidence: 73%
“…If DAT individuals were unable to represent effectively sentential context, then one might expect that they would suffer greater interference from contextually inappropriate meanings of ambiguous words because of their inability to use poorly represented context as a basis for discriminating between appropriate and inappropriate meanings. Previous studies have suggested that DAT individuals do have a decreased ability to use context to disambiguate words (Balota & Duchek, 1991;Cushman & Caine, 1987;Kempler, Curtiss, & Jackson, 1987). An impoverished representation of context may have caused less suppression of inappropriate meanings for DAT individuals than for healthy older individuals who presumably can effectively use context as a basis to suppress contextually inappropriate meanings.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of grammatical processing in AD have been controversial. Some work shows successful processing of syntax and grammar in these patients (Blanken, Dittman, Haas, & Wallesch, 1987;Illes, 1990;Irigaray, 1973;Kemper, LaBarge, Ferraro, Cheung, & Storandt, 1993;Kempler, Curtiss, & Jackson, 1987), while other reports describe grammatical impairments (Croot, Hodges, & Patterson, 1999;Emery & Breslau, 1989;Kempler, Almor, Tyler, Andersen, & MacDonald, 1998;Rochon, Waters, & Caplan, 1994). We and others find that AD patients have difficulty with grammatical processing, but experimental evidence attributes this to a limitation of the executive resources needed to process long-distance grammatical dependencies in a sentence.…”
Section: Preserved Grammatical Processing Of Novel Form Class Knowledmentioning
confidence: 84%
“…Interesting is the repeated observation that the grammatical aspects of language are largely spared in the early stages of Alzheimer disease (Appel, Kertesy, & Fishman, 1982;Kempler, Curtiss, & Jackson, 1987;Murillo Ruiz, 1999). Grammar is eventually degraded together with the progressive breakdown of conceptual aspects of language and the complete collapse of pragmatic regulation (Maxim & Bryan, 1994).…”
Section: Discussionmentioning
confidence: 99%